Social Media Use For Internal Communication In Kenyan Organizations - Moraa, Faith; Mbatha, Blessing (UIN Raden Mas Said Surakarta, 2024)
In today's digital era, the integration of social media into organizational communication practices is essential. The research aimed to assess the extent of social media adoption for internal communication, identify the platforms predominantly used, and evaluate their impact on communication efficacy within organizations Qualitative research methodology was adopted to capture a comprehensive view of social media usage in three organizations. Data were gathered through face-to-face interviews and focus group discussions with 48 participants, purposively sampled, employing thematic analysis to distill the insights. The findings reveal a selective adoption of platforms such as Slack and WhatsApp. While some employees embrace these digital tools, others persist with traditional methods. This contrast highlights reluctance within organizations to fully transition to digital communication tools. The study recommends that organizations strengthen digital literacy programs, establish clear usage policies, and foster an environment that balances innovative digital practices with established communication protocols.